(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The aim of the study was to investigate the relationship between ferritin levels in blood and follicular fluid and the quality of embryos obtained during in vitro fertilization (IVF) procedures. The study included 65 women aged 25 to 39 years with a diagnosis of infertility who underwent ovulation stimulation and ovarian puncture as part of standard IVF protocols. The participants were divided into two groups depending on the strategy of iron medication use: group 2A (iron + stimulation) and group 2B (iron - break - stimulation). Ferritin levels in blood and follicular fluid were analyzed comparatively, and the correlation between ferritin levels and the quality of embryos obtained was investigated. The results showed that high ferritin levels in follicular fluid correlated with an increase in the number of high quality embryos in group 2A, but excess iron could lead to a decrease in embryo quality. In group 2B, where ferritin levels were lower, there was a higher frequency of good quality embryos. The study confirms the importance of optimizing iron levels to improve IVF success and embryo quality.